A rare huge bladder inflammatory myofibroblastic tumor treated by en bloc resection with diode laser: a case report and literature review - Yuan, Huisheng; Wang, Zilong; Sun, Jiaxing; Chu, Junhao; Duan, Shishuai; Wang, Muwen (Frontiers in Oncology, 2024)
Background: Inflammatory myofibroblastic tumor (IMT) is a rare neoplasm with malignant potential. Bladder IMT is even rarer and mainly treated by surgical resection However, partial or radical cystectomy would affect the quality of life of patients due to major surgical trauma, and classical TURBT is hard to avoid intraoperative complications including obturator nerve reflex and bleeding etc. Therefore, the safe and effective better choice of surgical approaches become critical to bladder IMT.A 42-year-old male patient was admitted to the department of urology with persistent painless gross hematuria for more than 10 days without the presentation of hypertension.Preoperative routine urine examination of red blood cells was 7738.9/HPF (normal range≤3/HPF).CTU indicated a space occupying lesion (6.0 cm×5.0 cm) in the left posterior wall of the bladder with heterogeneous enhancement in the excretory phase. MRI also indicated bladder tumor with slightly equal SI on T1WI and mixed high SI on T2WI (6.0 cm×5.1cm×3.5cm) in the left posterior wall of the bladder. En bloc resection of bladder IMT with 1470 nm diode laser in combination of removing the enucleated tumor by the morcellator system was performed. Postoperative pathological examination revealed bladder IMT, with IHC positive for Ki-67 (15-20%), CK AE1/AE3, SMA, and Desmin of bladder IMT and negative for ALK of bladder IMT as well as FISH negative for ALK gene rearrangement. Second TUR with 1470 nm diode laser was performed within 6 weeks to reduce postoperative risk of recurrence due to highly malignant potential for the high expression of Ki-67 (15-20%) and negative ALK in IHC staining. The second postoperative pathology report showed chronic inflammation concomitant with edema of the bladder mucosa without bladder IMT, furthermore no tumor was observed in muscularis propria layer of bladder. No recurrence occurred during the period of 24-month follow-up.En bloc resection of bladder IMT in combination of the following second transurethral resection with 1470 nm diode laser is a safe and effective surgical approach for the huge bladder IMT with highly malignant potential.